2018
DOI: 10.1259/dmfr.20170323
|View full text |Cite
|
Sign up to set email alerts
|

CT Imaging Features of Antiresorptive agent-Related Osteonecrosis of the Jaw/ Medication-Related Osteonecrosis of the Jaws

Abstract: ARONJ/MRONJ has characteristic CT image findings which could be useful for its assessment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
35
1
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(59 citation statements)
references
References 35 publications
6
35
1
3
Order By: Relevance
“…MRONJ of the maxilla adjacent to the maxillary sinus is known to occur mucoperiosteal thickening and fistula formation. Similar to those studies, the patients of upper MRONJ in this study showed maxillary sinusitis on the same side (16) . When MRONJ contact the mandibular canal, previous studies have shown that it needed attention as it can cause symptoms such as inferior alveolar nerve palsy (19) .…”
Section: Subjectssupporting
confidence: 90%
“…MRONJ of the maxilla adjacent to the maxillary sinus is known to occur mucoperiosteal thickening and fistula formation. Similar to those studies, the patients of upper MRONJ in this study showed maxillary sinusitis on the same side (16) . When MRONJ contact the mandibular canal, previous studies have shown that it needed attention as it can cause symptoms such as inferior alveolar nerve palsy (19) .…”
Section: Subjectssupporting
confidence: 90%
“…To date, there is no evidence‐based surgical approach for BRONJ, due to the difficulty in distinguishing the boundaries of affected bones accurately in surgery. Although the preoperative imaging methods could be used to locate the affected region, the multifactorial pathogenesis and the non‐specific radiologic characteristics of BRONJ, especially in the earliest stages, may prevent from a successful surgical management (Baba et al, ; Migliorati, Brennan, & Peterson, ). Some researchers used to utilize tetracycline and its derivatives to guide surgical debridement of BRONJ (Ristow et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…Same as with femur situation, jawbones also imaging on 74 Japanese patients who su ered from ARONJ/ MRONJ showed that most lesions of ONJ were both lytic and sclerotic. Meanwhile, observative results of the same study revealed that the size of the sequestra were mostly small with some of them exhibited periosteal reaction, while cortical bone perforation was more commonly seen in buccolingual or buccal cortical bone other than lingual cortical bone [39]. Cone beam computed tomography (CBCT) analysis has also shown the lesions in MRONJ with thicker cortical bone and more sclerotic bone marrow [40,41].…”
Section: Trabecular Microarchitecturementioning
confidence: 91%